PENGEMBANGAN SUMBER DAYA MANUSIA DESA GADINGKULON KECAMATAN DAU KABUPATEN MALANG - Roro Merry Chornelia; Asih Widi Lestari; Yosilda Sarti Yoei (Universitas Tribhuwana Tunggadewi, 2023)
The development of human resources is a very important factor in improving the quality of village development. The increase in human resources in Indonesia is inseparable from village government governance. Development of human resources is a major factor in improving the quality of social life of the community. This study aims to determine the development of human resources in Gadingkulon Village, Dau District, Malang Regency. The type of research used is qualitative research using data collection techniques through interviews, observation and documentation. Sampling used perposive sampling, to test the validity of the data researchers used a triangulation technique. Data analysis was carried out by means of data reduction, data presentation, and drawing conclusions. The process of developing human resources in improving the development of Gadingkulon village can be done through a training process such as training in making yogurt, making fertilizer, and plant seeds. The development of human resources in the development of Gadingkulon Village that must be considered is the quality of education because education is the main key in increasing human resources as a driver, manager and in improving work performance.AbstrakPengembangan sumber daya manusia merupakan faktor yang sangat penting dalam meningkatkan kualitas pembangunan desa. Meningkatnya sumber daya manusia di Indonesia tidak terlepas dari tata kelola pemerintah desa. pengembangan Sumber daya manusia menjadi faktor utama dalam meningkatkan kualitas kehidupan sosial masyarakat. Penelitian ini bertujuan untuk mengetahui pengembangan sumber daya manusia desa Gadingkulon, Kecamatan Dau Kabupaten Malang. Jenis penelitian yang digunakan adalah penelitian kualitatif dengan menggunakan teknik pengumpulan data melalui wawancara, observasi dan juga dokumentasi. Pengambilan sampel menggunakan perposive sampling, untuk menguji keabsahan data peneliti menggunakan teknik triangulasi. Analisis data dilakukan dengan cara reduksi data, penyajian data, dan penarikan kesimpulan. Proses pengembangan sumber daya manusia Dalam meningkatkan pembanguan desa Gadingkulon dapat dilakukan melalui proses pelatihan seperti pelatihan dalam pembuatan yougurt, pembuatan pupuk, dan bibit tanaman. Pengembangan sumber daya manusia dalam pembangunan Desa Gadingkulon yang harus diperhatikan adalah kualitas pendidikan karena pendidikan merupakan kunci utama dalam meningkatkan sumber daya manusia sebagai penggerak, pengelola dan dalam meningkatkan kinerja kerja yang dimiliki.